2023
DOI: 10.3390/ani13071177
|View full text |Cite
|
Sign up to set email alerts
|

Beef Steers and Enteric Methane: Reducing Emissions by Managing Forage Diet Fiber Content

Abstract: Understanding the methane (CH4) emissions that are produced by enteric fermentation is one of the main problems to be solved for livestock, due to their GHG effects. These emissions are affected by the quantity and quality of their diets, thus, it is key to accurately define the intake and fiber content (NDF) of these forage diets. On the other hand, different emission prediction equations have been developed; however, there are scarce and uncertain results regarding their evaluation of the emissions that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
1
1
0
Order By: Relevance
“…Similar values were found by Santander et al (2023), by reducing the NDF of the diet by at least 10%. Gaviria et al (2020) also found lower emissions in animals consuming grass after a regrowth period of 45 days compared to those observed after a regrowth period of 65 days.…”
Section: Discussionsupporting
confidence: 84%
“…Similar values were found by Santander et al (2023), by reducing the NDF of the diet by at least 10%. Gaviria et al (2020) also found lower emissions in animals consuming grass after a regrowth period of 45 days compared to those observed after a regrowth period of 65 days.…”
Section: Discussionsupporting
confidence: 84%
“…This in vitro study is the first to consider the total production of gas and CH 4 using different percentages of red macroalgae from the Azores (Terceira Island) and using exclusively pasture-based feed (substrate), which was chemically characterised ( Table 1 ), emphasising the fibre content. This aspect is crucial to understand due to the observed positive correlation between fibre content and enteric methane production [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…171 For instance, increasing the amount of dietary fiber in the feed of beef steers increases enteric methane production. 172 Consequently, reducing the dietary fiber levels in feeds may have beneficial effects in terms of GHG emissions. However, the impact of changing an animal's diet or using feed additives on its health, productivity, and nutritional quality also needs to be considered.…”
Section: Nutritionmentioning
confidence: 99%
“…Researchers have also shown that the nature of the feed given to livestock animals impacts their GHG emissions . For instance, increasing the amount of dietary fiber in the feed of beef steers increases enteric methane production . Consequently, reducing the dietary fiber levels in feeds may have beneficial effects in terms of GHG emissions.…”
Section: Optimizing Livestock Productionmentioning
confidence: 99%